Studies of Cytotoxicity Effects, SARS‐CoV‐2 Main Protease Inhibition, and in Silico Interactions of Synthetic Chalcones. Issue 3 (14th February 2023) - Guterres Fernandes, Octavio L.; Tizziani, Tiago; Dambrós, Bibiana P.; Ferreira de Sousa, Natália; Mansur Pontes, Carime L.; da Silva, Layzon A. L.; Escorteganha Pollo, Luiz A.; de Assis, Francisco F.; Scotti, Marcus T.; Scotti, Luciana; Braga, Antonio L.; Steindel, Mario; et al.
Abstract: SARS‐CoV‐2 main protease (M pro ) plays an essential role in proteolysis cleavage that promotes coronavirus replication. Thus, attenuating the activity of this enzyme represents a strategy to develop antiviral agents. We report inhibitory effects against M pro of 40 synthetic chalcones, and cytotoxicity activities, hemolysis, and in silico interactions of active compounds. Seven of them bearing a ( E )‐3‐(furan‐2‐yl)‐1‐arylprop‐2‐en‐1‐one skeleton (10, 28, and 35–39 ) showed enzyme inhibition with IC50 ranging from 13.76 and 36.13 μM. Except for 35 and 36, other active compounds were not cytotoxic up to 150 μM against THP‐1 and Vero cell lines. Compounds 10, and 35–39 showed no hemolysis while 28 was weakly hemotoxic at 150 μM. Moreover, molecular docking showed interactions between compound 10 and M pro (PDBID 5RG2 and 5RG3) with proximity to cys145 and His41, suggesting a covalent binding. Products of the reaction between chalcones and cyclohexanethiol indicated that this binding could be a Michael addition type. Abstract :